Answer:
2x^2 + 3/2x -5
Step-by-step explanation:
f(x) = x/2 -2
g(x) = 2x^2 +x -3
f(x)+ g(x) = x/2 -2+ 2x^2 +x -3
Combine like terms
= 2x^2 + 3/2x -5
Answer:
-18y - 18
Step-by-step explanation:
The -2 needs to be distributed into both values in the parenthesis. This will make the equation -8y - 10y - 18. Then, you put the like terms together. This will result in the final equation, -18y - 18
Answer:
x = -1
Step-by-step explanation:
(-1 , 6) ; (-1 , -5)
There is no change in x-coordinate values.
So, the is parallel to y-axis
x = -1
Answer:
the answer would be 12
Step-by-step explanation:
It's 96%
816/850 = 0.96, which is 96%
Hope I helped! ( Smiles )